Evaluación morfológica de la fibra de lana de los ovinos en el ceypsa - Toapanta Yánez, Andrés Marcelo (2016)
This project was conducted in the province of Cotopaxi Parish Eloy Alfaro, in the Experimental and Production Salache Center of the Technical University of Cotopaxi, at the premises of sheep production with full United Nations of 39 animals between males and females, female animals which 9 was used. The objective was to evaluate morphologically fiber of sheep for which either we rely on to make a selection of sheep depending Phenotypic Characteristics and race Of Which Were Frisona, belly Black and Katahdin animals Each we can deduce from the United Nations earring Let us serves as reference and Accurate para Sampling that is data is done 2 times a year, can that I differentiate weighing animals according to the type of wool fiber with respective data As is the Do, longitudinal Diameter and chest, and legs Cruz. Data obtained after being evaluated respectively by means of a scale digital, whatever gave us the result of the weight A rule for OBSERVE Do LENGTH AND FINALLY stereoscope with the Chamber of Neubauer which allowed us to see the diameter in microns the diameter of the wool fiber is in intermediate average United Nations as the best wool of which is from the merino sheep has a diameter of 18 to 25 u and m result of the evaluation of the wool fiber from sheep in CEYPSA author of 18-30 U longitudinal....